Komik untuk Pengembangan Literasi Mahadata - Maulana Faris (Ultimacomm: Jurnal Ilmu Komunikasi, 2022)
Big data is one of the sources of information needed in responding to the challenges of very fast information needs in the era of the COVID-19 pandemic. However, communication tools are needed to build big data literacy in ordinary people in order to build public trust in big data. Comics are one of the communication tools that can embrace the wider community. Information about big data is made in the form of comic strips posted on social media, namely BPS official Facebook and Instagram. This research specifically discusses how science comics become a communication tool to build big data literacy in society. We found that community engagement was quite high when big data literacy content was made in the form of comics. Previous research was mostly limited to the classroom audience in schools/campus. This research is able to reach a wider and diverse community because it uses social media to help disseminate the content of big data comics. In the first edition, big data comics on Facebook managed to reach 17,495 accounts and 44,497 accounts on Instagram. The use of big data literacy comics posted through social media has sparked a lot of active discussion from the public. Research shows that increasing big data literacy through comics is a new and noteworthy approach that has been widely accepted by society.